An exploratory metaphor analysis on the perceptions of nursing students about the concept of aging - Yilmaz, Emel Bahadir; Yüksel, Arzu (Magyar Gerontológia, 2021)
Purpose: The aim of this study was to reveal the perceptions of nursing students about the concept of aging through metaphors.Methods: The basic qualitative research design was used to evaluate the metaphors of nursing students regarding the concept of aging from their perspectives. The study sample consisted of 104 senior nursing students at Aksaray University in the 2021-2022 academic year. A purposive sampling method was used. "Metaphoric Perceptions Data Collection Form", which was prepared by the researchers in line with the literature, was used as a data collection tool. The form consists of two parts. In the first part, the demographic characteristics of the students were investigated. In the second part, the sentence “Aging is like … because … ” was given to reveal students' metaphors regarding the concept of aging. The metaphors developed by the students regarding the concept of old age were analyzed and interpreted with Metaphor Analysis. Metaphor analysis has been associated with content analysis.Results: The mean age of the students participating in the study was 21.65±0.99 (min: 20, max: 25). Of students, 68.6% were female, 33.3% lived in city, and 84.3% had nuclear family. About half (50.0%) of their grandparents lived in their house. Of the students, 39.2% thought about living with your parents when you start a family in the future; 52.9% lived with older adults aged 65 and over until now; 92.2% cared for an older patient during clinical practice; and 74.5% wanted to work in a health institution serving the elderly after graduation. Students produced a total of 102 valid metaphors for the concept of aging. Four main themes were obtained from the data. The main themes were aging as an ending story, a need for care, attention, and support, a new beginning, and a source of life.Conclusion: Nursing students' metaphors about aging are generally negative, but also contain expressions of respect.